Bioaugmented Sand Filter Columns Provide Stable Removal of Pesticide Residue From Membrane Retentate - Ellegaard-Jensen, Lea; Schostag, Morten Dencker; Nikbakht Fini, Mahdi; Badawi, Nora; Gobbi, Alex; Aamand, Jens; Hansen, Lars Hestbjerg (Frontiers in Water, 2020)
Drinking water resources, such as groundwater, are threatened by pollution. The pesticide metabolite 2,6-dichlorobenzamide (BAM) is one of the compounds frequently found in groundwater. Studies have attempted to add specific BAM-degrading bacteria to sand filters at drinking water treatment facilities. This biotechnology has shown great potential in removing BAM from contaminated water. However, the degradation potential was formerly lost after approximately 2-3 weeks due to a decrease of the degrader population over time. The aim of the present study was to overcome the constraints leading to loss of degraders from inoculated filters. Our approach was threefold: 1) Development of a novel inoculation strategy, 2) lowering the flowrate to reduce washout of cells, and 3) increasing the concentration of nutrients hereunder the pollutant in a smaller inlet water stream. The two latter were achieved via modifications of the inlet water by applying membrane treatment which, besides producing an ultra-pure water fraction, produced a residual water stream with nutrients including BAM concentrated in an approximately 10-fold reduced volume. This was done to alleviate starvation of degrader bacteria in the otherwise oligotrophic sand filters and to enable a decreased flowrate. By this approach, we achieved 100% BAM removal over a period of 40 days in sand filter columns inoculated with the BAM-degrader Aminobacter sp. MSH1. Molecular targeting of the degrader strain showed that the population of degrader bacteria persisted at high numbers throughout the sand filter columns and over the entire timespan of the experiment. 16S rRNA gene amplicon sequencing confirmed that MSH1 dominated the bacterial communities of the inoculated sand filter columns at experimental termination. The community composition of the indigenous prokaryotes, based on beta diversity, in the sand filter columns was governed by the feed water type i.e. membrane retentate or untreated water.